Privação de liberdade e o acesso à saúde: o desafio da intersetorialidade - Dantas, Andreza Carla da Silva (2012)
Adolescents deprived of liberty under socio-through closed-Educational Center of the Adolescent (ECA), belonging to FUNDAC, have different needs for its development, among these needs, health. These needs are brought by the Child and Adolescent (ECA) as guarantees and rights that must be provided in full. However, what is perceived is the camouflage of such guarantees due to stigma and prejudice that permeates socio reality. In this perspective, the study brought the objective of analyzing the process of intersectoral relationships built from the cross between the politics of health and social protection policy adolescents deprived of freedom, in view of the expansion of social rights and thus outline how intersectoral action are drawn between management levels. We decided to conduct a search of an exploratory nature, given that the theme is not explored, especially in terms of an intersectoral approach. Also, do not nullify the bibliographic and documentary research, as this is the starting point for a preliminary understanding. For data analysis, we use the qualitative dimension in order to intensify the study, not being exempted from a quantitative approach. With respect to the instruments of data collection forms used for each group of respondents: Professional Education Center Adolescent (ECA), with 28% sample of the universe; professionals in public health network represented by the specialists of the Municipal Hospital Santa Isabel and the Center for Integrated Healthcare (CAIS Jaguaribe) whose universe was 104 professionals, the sample was 15% of the universe. Regarding the choice of the group of professionals in the public health system, was a survey of referrals to the demands and thus identified the referral services to which adolescents are repeatedly referred for specialized care. The study results showed that the normative point of view and documentary is actually built plans and specifications that address the health care of adolescents deprived of freedom in Paraíba. Furthermore, the investigated reality is pervaded by significant gaps and weaknesses in how access to the health of adolescents is provided. The professionals can identify the lack of dialogue between social policies and their impacts, caused by the lack of intersectoral actions. With respect to managers, it was realized that there is dialogue regarding the creation of the State Operating Plan (POE) with a view to systematizing and promoting the health of adolescents in conflict with the law, however not yet been translated into a building intersectoral, given the no involvement of other actors and sectors of administration. One can then conclude from the fact that the intersectoral investigated is of an immense challenge, because access to the health of the adolescent becomes a practice based on the law, this view should be the three management levels and their respective institutions and organs of social control.